Legal Protection of BP Batam Port Assets from the Perspective of the Security Directorate - Bahtiar, Bahtiar; Maileni, Dwi Afni; Riyanto, Agus; Bhakti, Rizki Tri Anugrah (Dinasti Research, 2026)
Abstract: This article examines the legal protection of BP Batam’s port assets from the perspective of the Security Directorate (Ditpam), focusing on civil liability, administrative safeguards, and coordination. Batam’s port infrastructure forms part of a strategic free-port regime and therefore constitutes state assets essential to logistics, investment, and connectivity. The study asks how the legal status of those assets is constructed, how Ditpam functions within the institutional framework, and what legal remedies are available when assets are damaged, occupied, misused, or exposed to governance failures. The research employs a normative juridical method based on statutory, conceptual, and institutional analysis, supported by official reports and relevant empirical materials. The analysis shows that BP Batam’s port assets enjoy a relatively strong legal foundation because they form part of state property managed under a special regulatory regime. Nevertheless, effective protection depends not only on formal ownership status but also on security supervision, orderly land administration, lawful asset utilization, and timely coordination with other authorities. The article concludes that legal protection will remain incomplete unless regulatory clarity, institutional capacity, and governance accountability are strengthened simultaneously.